1998
DOI: 10.1111/1467-9787.00093
|View full text |Cite
|
Sign up to set email alerts
|

Transport Costs and Rural Development

Abstract: Innovations that reduce costs of transport from rural locations may also reduce transport costs to rural areas. As transport costs fall, producers can afford to concentrate and achieve economies of scale. This paper explains an initially negative, but ultimately positive, relationship between reductions in transport costs and rural development. A two‐region general equilibrium model with firm and worker spatial mobility highlights the firm and household location implications of costly transport‐service use by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 19 publications
5
68
0
6
Order By: Relevance
“…In the first one, when workers' migration costs are sufficiently large (δ is such that γ > 2 Cδτ (τ * − τ )), the outcome of the migration dynamics is the same as the one described in Section 3.3. In other words, the equilibrium path is not consistent with (29), thus implying that expectations do not matter.…”
Section: On the Impact Of Forward-looking Behaviormentioning
confidence: 98%
See 3 more Smart Citations
“…In the first one, when workers' migration costs are sufficiently large (δ is such that γ > 2 Cδτ (τ * − τ )), the outcome of the migration dynamics is the same as the one described in Section 3.3. In other words, the equilibrium path is not consistent with (29), thus implying that expectations do not matter.…”
Section: On the Impact Of Forward-looking Behaviormentioning
confidence: 98%
“…It is worth stressing that the reasons that lead to dispersion in the first and third phases are different: in the former, the modern sector is dispersed because the cost of shipping its output is high; in the latter, dispersion arises because the periphery develops some comparative advantage in terms of labor cost. (Kilkenny, 1998). For example, if both costs decrease proportionally, it can be shown that re-dispersion never occurs.…”
Section: On a ∩-Shaped Relationship Between Agglomeration And Transpomentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the congestion effect is largely ignored in the Krugman type approach, which would also favor dispersion after a certain threshold. The existence of other rural activities than agriculture, for which transportation costs are different, may invert the dynamics and generate dispersion forces, as illustrated by Kilkenny (1998).…”
Section: Factors Suggesting Brighter Prospects For Rural Areasmentioning
confidence: 99%